2022
DOI: 10.1109/jphotov.2022.3189327
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Antireflection Coatings for Cover Glass on Silicon Solar Modules

Abstract: The cover glass on solar modules provides protection for the underlying solar cells but also leads to two forms of power loss: reflection losses and soiling losses. In this work we report on the design of a broadband multilayer anti-reflection (MAR) coating designed for use with silicon modules and its advantages over commercial porous SiO2 sol-gel coatings. The six-layer anti-reflection coating comprising SiO2 and ZrO2 has then been deposited on glass using high-rate pulsed DC magnetron sputtering. The reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The transmission and reflection coefficients for thin film stacks can be calculated, if the refractive index (n) and extinction coefficient (k) of the thin film materials are known, and this provides the basis for the modelled reflectance curves shown in this work. This modelling approach has been used in previous work [14], [17] for the development of MAR coatings, and also in other studies focused on the optimisation of various layers in a PV device [23].…”
Section: Coating Design and Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission and reflection coefficients for thin film stacks can be calculated, if the refractive index (n) and extinction coefficient (k) of the thin film materials are known, and this provides the basis for the modelled reflectance curves shown in this work. This modelling approach has been used in previous work [14], [17] for the development of MAR coatings, and also in other studies focused on the optimisation of various layers in a PV device [23].…”
Section: Coating Design and Modellingmentioning
confidence: 99%
“…The use of fully dense layers gives advantages such as higher abrasion resistance and protection against moisture ingress. MAR coatings have previously been designed for silicon, CdTe, and other thin film PV technologies giving relative improvements in J sc as high as 3.8% [14]- [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some organic materials with −CH 3 groups were also added into a SiO 2 precursor sol to modify the structure of SiO 2 films, changing the physical connection into chemical bond links among SiO 2 particles and thus improving the mechanical performance of the film. Furthermore, multilayer antireflection (MAR) coatings have been reported, which achieved good reduce-reflection effects over an extended wavelength range. Law et al reported a six-layer AR design and materials used for each coating layer and their respective thicknesses not the scale . However, there is no doubt that selection of materials and designs of thicknesses for multilayer films would increase the complexity of the preparation process of AR coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium dioxide (ZrO 2 ) has amazing properties such as wide band gap, thermal stability, and high refractive index. , Moreover, ZrO 2 is a potentially modified material with excellent mechanical performances, which can promote anti-corrosion ability through enhancing thermal stability and enlarging surface area . In this work, a ZrO 2 –SiO 2 composite film as an antireflection layer with enhanced pencil hardness and higher transmittance gain was successfully prepared by a facile sol–gel method, comparing with the pure SiO 2 film synthesized with the same alkali-catalyzed method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation